Development of Gamification-Based Learning Media on Environmental Change Topics for Senior High School Students - Afiwiyuna Afiwiyuna; Abdullah Abdullah; Ismul Huda (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a gamification-based learning medium and to examine the feasibility of its use in teaching environmental change topics for senior high school students. A quantitative approach was applied using the Research and Development (R&D) method with the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects were 35 tenth-grade students of SMA Negeri 3 Banda Aceh. The research instruments included validation sheets completed by media and subject-matter experts, as well as a student response questionnaire using a Likert scale ranging from 1 to 5. The validation results indicated that the developed media achieved a very high level of feasibility, with a score of 98.9% from the media expert (excellent category) and 86.4% from the material expert (very valid category). The student trial results showed scores of 91.43% for learnability, 88.00% for efficiency, 86.71% for interaction, 80.38% for errors, and 83.43% for satisfaction, all of which fell into the excellent category. In addition, content feasibility reached 90%, language feasibility 90%, presentation feasibility 88.46%, and graphic feasibility 91.57%, resulting in an overall feasibility score of 84.78% in the very feasible category. The average score of students’ test answers within the application reached 91.09. Therefore, the gamification-based media Savior of the Earth is considered feasible as an interactive learning tool for environmental change material